Social Media Marketing: Peranannya Dalam Meningkatkan Kinerja UMKM di Kota Malang Pada Masa Pandemi Covid-19 - Handoko, Elvanda Satria Pratama; Mukhlis, Imam (Universitas Proklamasi 45, 2025)
The Covid-19 pandemic in Indonesia has caused crises in various sectors, including health, education, and the economy. SMEs play a crucial role in promoting economic growth and achieving national stability. At this time, there are many buying and selling activities that use digital media, because it makes it easier for both consumers and SMEs themselves. This study aims to analyze the role of social media marketing in improving performance in several SMEs in Malang City during the Covid -19 pandemic. This study used qualitative methods, while the data obtained were based on primary data. The data collection technique used is the triangulation technique, while the sample is taken using purposive sampling, with the criteria of informants, namely SMEs in Malang City who have implemented social media marketing. There are several benefits obtained by MSME actors in implementing social media marketing during the Covid -19 pandemic. First, social media can be used as an effective and efficient promotional medium. Second, social media marketing can also build brand awareness by consistently running promotions on social media. Third, research informants agreed that implementing social media marketing during the Covid -19 pandemic was effective in increasing SMEs' sales. Restrictions on people's activities in Indonesia during the pandemic have made consumers who buy products from social media tend to increase.